The Coefficient of the Generating Function in the Form of a Lower Hessenberg Matrix - Khasanah, Nur; Yazidah, Izzatul; Masvika, Hendra (JMT (Jurnal Matematika dan Terapan), 2024)
This study aims to obtain the generating function with the lower Hessenberg matrix coefficients. The method used is to use Cramer's rule. The result of this research is the generating function which consists of a power series which is a collection of several terms.